Effect of Service Quality on Satisfaction of Inpatient BPJS Health Participants Non PBI in Medan Methodist - Carolina Hanna; Arifah Devi Fitriani; Asriwati Asriwati (Science Midwifery, 2022)
Non-PBI Health quality of hospital services is an important element in health services. Hospitals are required to provide quality services as health service providers who play an active role and participate in supporting health development goals. The development of the BOR (Bed Occupancy Rate) of inpatients experienced an up and down trend at Methodist Hospital in 2017-2019. In 2017 it was 30.9%, in 2018 it was 34.2%, in 2019 it was 56.3% and it had not reached the 60-85% standard. This research was a quantitative research with cross-sectional design. The population were all inpatients of BPJS Kesehatan non-PBI participants at Methodist Hospital Medan. The total population was 126 people and the entire population as the sample. Data were analyzed by multiple logistic regression at .05. The results showed statistically that the variables of reliability, responsiveness, empathy, appearance, processes and policies had a significant effect on the satisfaction of inpatients of BPJS Kesehatan non-PBI participants at the Medan Methodist Hospital. The variable that has a major influence on the satisfaction of inpatients of BPJS Kesehatan non-PBI participants is the process dimension with an OR value of 27.864. It was recommended to Medan Methodist Hospital: 1) seek to increase the dimensions of the process through making local Standard Operating Procedures (SOP) for all hospital health workers, 2) seek to increase the dimensions of reliability, responsiveness, empathy, appearance and policy through increasing the role of Home Health Promotion Sickness (PKRS) as well as seeking service excellent training to improve the ability of health workers to communicate.